Corporate social responsibility in agro-processing and garment industry: Evidence from Ethiopia - Anteneh Mulugeta Eyasu (Taylor & Francis Group, 2020)
Currently, large industries like agro-processing and garment (Textile and Leather) industries in Ethiopia have interested to implement CSR activities. Hence, this study examined the causal relationship between stakeholders’ and CSR implementation in agro-processing and garment industries based on employees’ perceptions. After reviewing several works of literature we developed CSR implementation measurements. For analysis of CSR implementation, a total of 891 respondents were taken from agro-processing and garment industries of the Amhara region, Ethiopia. Then we applied frequency, percentage, Confirmatory factor analysis and structural equation model for this data analysis. The empirical result showed that environment, customer, owner/shareholder, community have a significant positive effect on CSR implementation in agro-processing and garment industries. However, it was also confirmed that employees have a negative significant effect on CSR implementation. Consider identified evidence of determinant factors of CSR implementation, managers of agro-processing and garment industries should take actions to improve CSR implementation and to alleviate those problems.